Geochemical Characterizations of Crude Oils in Pendopo High and Limau Graben, South Sumatra Basin - Syaifudin, Muhammad; Subroto, Eddy A. (Indonesian Journal on Geoscience, 2024)
There are several oil fields in Pendopo High and Limau Graben, South Palembang Subbasin, South Sumatra Basin. Crude oils from the Pendopo High and Limau Graben have been analyzed using geochemical methods. Some or all of the following analyses were completed on twenty-four oils. Two analysis methods, namely the δ13C isotopic and biomarker compositions have been used to classify the oil types. Most of the oils are isotopically more depleted in δ13C sat (> -28‰) relative to the other four oil sample counterpart of the Pendopo High. All oil samples from The Pendopo High have Pr/Ph values < 4 and those from the Limau Graben > 4. In addition, biomarker ratio for hopanes/steranes from the Limau Graben shows small values compared with the Pendopo High. Geochemical cross plots of probabilities can also be used to distinguish oils derived from different source inputs. In the Limau Graben, tricyclic terpane data shows terrestrial patterns, while the Pendopo High shows deltaic patterns. The Limau Graben is derived from humic kerogen, while the Pendopo High is more towards mixed kerogen (humic and sapropelic kerogen). The depositional condition in the Limau Graben is anoxic to suboxic to oxic and mostly oxic condition, predominated by higher plants. While Pendopo High condition is anoxic to suboxic, predominated by algae. Oil in the Pendopo High is interpreted to be deltaic oil, whereas oil in the Limau Graben is a typical fluvial.